2023
DOI: 10.1007/s12393-022-09329-9
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Cold Plasma Technology in Low-Moisture Foods

Abstract: Low-moisture foods such as spices, grains, and seeds constitute an important part of the human diet. Increased consumer concern for food safety and food quality has focused on the decontamination technologies required for low-moisture foods. Cold plasma treatment has been a promising novel technology in the food processing industry due to its advantages in safety, efficiency, versatility, and environmentally friendly nature. It has shown various capabilities on safety and quality control in low-moisture foods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 178 publications
0
3
0
Order By: Relevance
“…Also, the generated reactive species during MACP treatment oxidize organic molecules present in the BMF. While oxidation typically leads to water loss, the exact mechanism by which this treatment reduces overall moisture content requires further investigation (Rao et al, 2023). The carbohydrate content decreased with the increment in applied voltage and duration as demonstrated in Table 2.…”
Section: Proximate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the generated reactive species during MACP treatment oxidize organic molecules present in the BMF. While oxidation typically leads to water loss, the exact mechanism by which this treatment reduces overall moisture content requires further investigation (Rao et al, 2023). The carbohydrate content decreased with the increment in applied voltage and duration as demonstrated in Table 2.…”
Section: Proximate Analysismentioning
confidence: 99%
“…Interestingly, the highest reduction (321.31 mg/100 g) was observed at the intensity (30 kV, 20 min). The observed decrease in antinutrients is likely due to the action of reactive species generated during MACP treatment (Rao et al, 2023). These reactive species, including free radicals and charged particles, can cleave glycosidic bonds in tannins and disrupt the phytate ring structure.…”
Section: Antinutrient Factorsmentioning
confidence: 99%
“…It has been demonstrated that cold plasma treatment can reduce Salmonella, Escherichia coli, Listeria monocytogenes, and Staphylococcus aureus by more than 5 logs (Rao et al, 2023). According to Niemira (2012), the efficacy of this treatment varies depending on the particular food type and processing conditions.…”
Section: Decontamination Of Foodsmentioning
confidence: 99%
“…Also, CP is composed of various excited atomic, molecular, ionic, and radical species, coexisting with numerous reactive species such as electrons, positive and negative ions, free radicals, gas atoms, molecules in ground or excited states, and quanta of electromagnetic radiation (UV photons and visible light) 6 . CP finds diverse applications in medicine, materials science, and environmental engineering, showcasing potential benefits in wound healing, cancer treatment, sterilization, surface modification, and material functionalization 7 . Dielectric Barrier Plasma (DBD), characterized by a dielectric material between electrodes, allows controlled and localized plasma discharge.…”
Section: Introductionmentioning
confidence: 99%